Pemanfaatan Media Digital dalam Pembelajaran Pendidikan Agama Islam di Era Society 5.0 - Rosdialena; Mhd Zidan Firmansyah (4, 2026)
tract The Society 5.0 era has brought significant changes to various aspects of life, including education. The increasingly rapid development of digital technology requires the educational sector to adapt by utilizing various digital media as effective, innovative, and relevant learning tools to meet students' needs. In the context of Islamic Religious Education (PAI), the use of digital media is a crucial strategy for improving the quality of learning, expanding access to learning resources, and instilling Islamic values ​​in a more engaging and contextual manner. This study aims to analyze the use of digital media in Islamic Religious Education learning in the Society 5.0 era, identify the various forms of digital media used, and examine the opportunities and challenges faced in their implementation. This study used a qualitative approach with library research methods. Data were obtained from various scientific sources such as books, journals, articles, and documents relevant to the research theme. Data analysis was conducted using data reduction techniques, data presentation, and descriptive-analytical conclusions. The results indicate that the use of digital media in PAI learning can improve the effectiveness of the teaching and learning process through the use of online learning platforms, Islamic educational applications, learning videos, social media, e-books, and various other digital learning resources. Digital media enables students to have a more interactive, flexible, and learner-centered learning experience. Furthermore, the integration of digital technology into Islamic Religious Education (PAI) learning can support the development of 21st-century skills, such as digital literacy, critical thinking, creativity, collaboration, and communication. Abstrak Era Society 5.0 menghadirkan perubahan signifikan dalam berbagai aspek kehidupan, termasuk bidang pendidikan. Perkembangan teknologi digital yang semakin pesat menuntut dunia pendidikan untuk beradaptasi dengan memanfaatkan berbagai media digital sebagai sarana pembelajaran yang efektif, inovatif, dan relevan dengan kebutuhan peserta didik. Dalam konteks Pendidikan Agama Islam (PAI), pemanfaatan media digital menjadi salah satu strategi penting untuk meningkatkan kualitas pembelajaran, memperluas akses terhadap sumber belajar, serta menanamkan nilai-nilai keislaman secara lebih menarik dan kontekstual. Penelitian ini bertujuan untuk menganalisis pemanfaatan media digital dalam pembelajaran Pendidikan Agama Islam di Era Society 5.0, mengidentifikasi berbagai bentuk media digital yang digunakan, serta mengkaji peluang dan tantangan yang dihadapi dalam implementasinya. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research). Data diperoleh dari berbagai sumber ilmiah seperti buku, jurnal, artikel, dan dokumen yang relevan dengan tema penelitian. Analisis data dilakukan melalui teknik reduksi data, penyajian data, dan penarikan kesimpulan secara deskriptif-analitis. Hasil penelitian menunjukkan bahwa pemanfaatan media digital dalam pembelajaran PAI dapat meningkatkan efektivitas proses belajar mengajar melalui penggunaan platform pembelajaran daring, aplikasi edukasi Islami, video pembelajaran, media sosial, e-book, serta berbagai sumber belajar digital lainnya. Media digital memungkinkan peserta didik memperoleh pengalaman belajar yang lebih interaktif, fleksibel, dan berpusat pada peserta didik. Selain itu, integrasi teknologi digital dalam pembelajaran PAI mampu mendukung pengembangan keterampilan abad ke-21, seperti literasi digital, berpikir kritis, kreativitas, kolaborasi, dan komunikasi.